2010
DOI: 10.1021/jz1011884
|View full text |Cite
|
Sign up to set email alerts
|

Roaming Pathway Leading to Unexpected Water + Vinyl Products in C2H4OH Dissociation

Abstract: We report molecular dynamics simulations of the unimolecular dissociation of energetic C2H4OH radicals using a full-dimensional potential energy surface (PES) fit to density functional theory (DFT) and coupled cluster (CCSD) calculations. Quasiclassical trajectories are initiated on the surface using microcanonical sampling at a total energy of 85.0 kcal/mol (44.1 kcal/mol relative to the zero-point energy). The trajectories reveal a roaming channel leading to the formation of water. The transition state (TS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
89
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(97 citation statements)
references
References 46 publications
8
89
0
Order By: Relevance
“…[2][3][4][5][6][7] For the molecules where all atoms are identical (allotropes) this should be the method of choice. 8 It allows reducing significantly the number of ab initio data points needed for accurate surface representation, as well as automatically takes care of the intrinsic molecular symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] For the molecules where all atoms are identical (allotropes) this should be the method of choice. 8 It allows reducing significantly the number of ab initio data points needed for accurate surface representation, as well as automatically takes care of the intrinsic molecular symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…This speculation was confirmed in 2004 by combined experimental and theoretical studies [95]. Since its discovery, this channel named "roaming" has been a hot topic as a new type of reaction mechanism [96][97][98], and it has been found in many reactions having implications to atmospheric chemistry [99][100][101][102][103][104][105][106][107][108] and combustion chemistry [88,109,110]. The IC was postulated to occur in the potential well of H 2 CO in many previous studies.…”
Section: Photodissociation Of Formaldehydementioning
confidence: 90%
“…Recent studies, both theoretical and experimental, have attempted to determine branching ratios of the product channels of the reaction, beginning at the CH 2 CH 2 OH (β-hydroxyethyl) radical adduct. 23,29,30 The CH 2 CH 2 OH radical intermediate may be produced from the photodissociation of 2-haloethanols. Hintsa et al 31 were the first to investigate the photodissociation of 2-bromoethanol at 193 nm, showing that a large fraction of β-hydroxyethyl radicals were formed stable to subsequent dissociation to OH + ethene and attributing it to a large partitioning of energy into rotational energy of the radicals.…”
Section: Introductionmentioning
confidence: 99%
“…We proposed that the dissociation of the radical to H 2 O + C 2 H 3 observed in our experiments might involve a frustrated dissociation of the C−O bond toward the [CH 2 CH 2 ]··· OH exit channel followed by an H atom abstraction by the OH moiety instead of returning to the CH 2 CH 2 OH well. In classical trajectory calculations on the global potential energy surface for this reaction, Kamarchik et al 30 observed a roaming mechanism for the H 2 O + vinyl product channel beginning from the radical intermediate. However, their calculations at 44 kcal/mol predicted a smaller branching to these products than was observed experimentally.…”
Section: Introductionmentioning
confidence: 99%